Input Technologies and Techniques (2002) - Hinckley, Ken (The Human-Computer Interaction Handbook: Fundamentals, Evolving Technologies and Emerging Applications (Human Factors and Ergonomics), 2002)
The Human-Computer Interaction Handbook: Fundamentals, Evolving Technologies, and Emerging Applications is a comprehensive survey of this fast-paced field that is of interest to all HCI practitioners, educators, consultants, and researchers. This includes computer scientists; industrial, electrical, and computer engineers; cognitive scientists; experimental psychologists; human factors professionals; interface and systems designers; product managers; and executives working with product development. This new Handbook offers a comprehensive compendium of foundational principles, as well as the most recent advances in conceptualizing, designing, and evaluating computing technologies. It spans a variety of traditional and non-traditional platforms, including desktop and mobile computing, networked and virtual environments, and information appliances. In addition, the volume offers thorough coverage of interaction issues concerning diverse users, including men; women; children; the elderly; and those with cognitive, physical, and perceptual impairments. Another unique feature of this new Handbook is that HCI is presented in the context of special application domains, such as e-commerce, telecommunication, government, health care, educational software, entertainment, games, motor vehicles, and aerospace. In this volume, an unprecedented number of top experts in the field of HCI share their expertise, experience, and insight regarding research, technological advancements, and specific methodologies in the field of human-computer interaction.